STORY COMPLETION: A TECHNIQUE IN TEACHING SPEAKING - Salmon J Hukom (Jurusan Pendidikan Bahasa dan Seni FKIP Universitas Pattimura, 2019)
In general, to achieve goals in teaching and learning the teachers can prepare appropriate strategy. This paper discusses a teaching and learning medium of speaking through story completion technique. By using this technique, it can be one of the exciting activities for motivating students in learning English confidently, especially speaking. The technique has activities which enable students to convey their ideas and all students obtain the same opportunities to speak at every meeting. The activities are oral activities that make student relax, happy and fun. The technique equips the students who have good English grammar and have sufficient vocabulary to explore their ideas in speaking. It does not mean that Story Completion technique cannot be used for students who have low English competence. The English teachers could manipulate the class by providing students with vocabularies of certain topic and tenses they will use in their speaking before running the meeting with this technique